Communicating with disabled children when inpatients: barriers and facilitators identified by parents and professionals in a qualitative study. (24th August 2014) - Sharkey, Siobhan; Lloyd, Claire; Tomlinson, Richard; Thomas, Eleanor; Martin, Alice; Logan, Stuart; Morris, Christopher
Abstract: Background: Communication is a fundamental part of health care, but can be more difficult with disabled children. Disabled children are more frequently admitted to hospital than other children. Aims: To explore experiences of ward staff and families to identify barriers and facilitators to effective communication with disabled children whilst inpatients. Design: This was an exploratory qualitative study. Methods: We consulted 25 staff working on paediatric wards and 15 parents of disabled children recently admitted to those wards. We had difficulty in recruiting children and evaluating their experiences. Data were collected through interviews and focus groups. A thematic analysis of the data supported by the Framework Approach was used to explore experiences and views about communication. Emerging themes were subsequently synthesised to identify barriers and facilitators to good communication. Results: Barriers to communication included time, professionals not prioritising communication in their role and poor information sharing between parents and professionals. Facilitators included professionals building rapport with a child, good relationships between professionals and parents, professionals having a family‐centred approach, and the use of communication aids. Conclusions: Communication with disabled children on the ward was perceived as less than optimal. Parents are instrumental in the communication between their children and professionals. Although aware of the importance of communication with disabled children, staff perceived time pressures and lack of priority given to communicating directly with the child as major barriers.